General Microbiology - Bruslind, Linda (Open textbook library., 2020)
Welcome to the wonderful world of microbiology! Yay! So. What is microbiology? If we break the word down it translates to “the study of small life,” where the small life refers to microorganisms or microbes. But who are the microbes? And how small are they? Generally microbes can be divided in to two categories: the cellular microbes (or organisms) and the acellular microbes (or agents). In the cellular camp we have the bacteria, the archaea, the fungi, and the protists (a bit of a grab bag composed of algae, protozoa, slime molds, and water molds). Cellular microbes can be either unicellular, where one cell is the entire organism, or multicellular, where hundreds, thousands or even billions of cells can make up the entire organism. In the acellular camp we have the viruses and other infectious agents, such as prions and viroids. In this textbook the focus will be on the bacteria and archaea (traditionally known as the “prokaryotes,”) and the viruses and other acellular agents.